Effect of proprioceptive and strength exercises on calf muscle endurance, balance and ankle angle applied: latin dancers - PINAR, YELİZ (My University, 2022)
The aim of the study was to examine the effect of proprioceptive and strength exercises applied in addition to dance exercises on the endurance of calf muscles, balance and ankle angles. Participants were randomly divided into two groups as Training Group (n=14; 7 males, 7 females) and Control Group (n=13; 7 males, 6 females). The training group performed a 12-week training programme that included proprioceptive and strength exercises twice a week, just before dance training. Anthropometric measures, static-dynamic balance tests, single heel rise test and 3D kinematic tests were conducted. When the groups were compared, significant changes were observed in the double leg dynamic balance values of the training group, right leg dynamic balance values of the control group, and left leg dynamic balance values of both groups (p < 0.05). When ankle angles were compared, the first single heel rise and angle of movement of the last single heel rise values of the training group differed significantly (p < 0.05). The balance performance and calf muscle endurance of the dancers can be improved with proprioceptive and strength training, which can contribute positively to movements during the dance.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Social Sciences and Humanities; Sociology; SOSYAL BİLİMLER, İNTERDİSİPLİNER; Sosyal Bilimler Genel; Sosyal Bilimler (SOC); SOCIAL SCIENCES, INTERDISCIPLINARY; SOCIAL SCIENCES, GENERAL; Social Sciences (SOC); Sosyal Bilimler (çeşitli); Genel Sosyal Bilimler; Teknoloji ve İnovasyon Yönetimi; Yönetim Bilgi Sistemi; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences (miscellaneous); General Social Sciences; Management of Technology and Innovation; Management Information Systems; Social Sciences & Humanities; Static balance; Dynamic balance; Heel rise; Latin dancers; Proprioception; TRAINING-PROGRAM; DYNAMIC BALANCE; PERFORMANCE; HOCKEY; FOOT